The Prophet Muḥammad’s Covenant with Yūḥannah Ibn Ru’bah and the Christians of Aylah - Abdalrahman Abulmajd (Religions, 2021)
This article examines the Prophet Muḥammad’s covenant with Yūḥannah, Prince of Aylah, and illustrates the role it plays in understanding religious pluralism and civil rights as envisioned in Prophet Muḥammad’s dream of a “Muslim Nation”. The article also briefly makes use of other covenants contracted between the Prophet and other Arab Christian tribes. The covenants reveal Prophet Muḥammad’s desire for religious pluralism and the granting of rights to all people, regardless of religion, creed, or personal practices. Although Prophet Muḥammad’s covenants with the Christians of his time are used as a framework of analysis in this article, these documents have not received as much attention as they deserve, as few researchers in our time have shown interest in them. Early manuscripts and historical sources, both Arab and Western, are referenced in order to explore the circumstances and consequences of these early correspondences between Islam’s final Prophet and contemporary Arab Christians. The findings of this investigation are significant in that the covenants serve as critical milestones and reminders in light of current discussions about relations between Muslims and Christians. The contents of the covenants can also be used as models for improving relations between Muslims and Christians in religiously diverse communities the world over.